Identifikasi protozoa parasitik di saluran pembuangan air limbah rumah tangga Kota Palangka Raya - Aroonasyaka, Rama; Kurniawan, Abdul Basith; Fortuna, Agnes Tasia; Tobing, Anggi Aprelia; Carolin, Angie Aprilia; Ayu, ⁠Anjelia Putri; Tukat, Cecilia Luvinska Christine; Sari, Dewi Marta Puspita; Feddly, Ello Christa; Jonathan , Farrel Yovan; Gunawan; Juantri, Jodie Mardhika; Ditara, Mutia; Meyliano, Raymondus Rio; Hadid, Ryan Al; Ariani, Sita (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2024)
Gastrointestinal protozoan infections are still a health problem throughout the world, especially in developing countries such as Indonesia. Pahandut Village and Kereng Bengkirai Village are located close to river flows that people use in their daily lives. This research aims to identify parasitic protozoa in waste disposal channels. The method used in this research is a descriptive method with an observational design, using a grab sampling technique. The protozoa obtained during sampling consisted of two types of protozoa, namely Blastocytis sp and Entamoeba hystolitica which came from Pahandut Village and Kereng Bengkirai Village. It is hoped that the results of this research can become data for further research and make people aware to be more selective in using water